When the Bubble Bursts: A Spatial Interrogation of Spanish Crisis in José Ángel Mañas’ Sospecha - Nick Phillips (Studies in 20th & 21st Century Literature, 2019)
José Ángel Mañas’s detective novel Sospecha investigates the consequences of the 2008 economic crisis by focusing on the unsustainable development of the Madrid urban area. I argue that the novel’s depiction of the Spanish capital serves as a case study for coming to terms with the identity and effects of crisis. By employing elements of the police procedural, Sospecha creates multiple trajectories through these suburban communities, allowing the novel to trace the impacts of a globalized economic model that presents these spaces as products of consumption. In turn, it is the spatial production of the city’s urban periphery that becomes the crime under investigation. However, the cause of the crimes themselves remain unresolved, suggesting a pessimistic and ultimately powerless interrogation of the social and economic factors that fuel the crisis and also impede Spain’s recovery.
Keywords: Spain; José Ángel Mañas; Sospecha; crime fiction; urban space; Madrid; globalization; immigration